(untitled) (Revista de Ciências Agroveterinárias, 2012)
The knowledge of the soil fertility conditions is fundamental to elaborate regional fertilization strategies for the main crops cultivated. To characterize the soil fertility conditions in the Santa Catarina State, Southern Brazil, it was interpreted the availability of some macro and micronutrients from levels determined in chemical analyses of soil sampled in the majority of the microcatchments with actuation of the project named “Programa de Recuperação Ambiental e de Apoio ao Pequeno Produtor Rural – PRAPEM/MB2”. In each microcatchment they were sampled four fields of two more representative crop systems in the summer-fall season of 2008, totalizing 6,894 fields. The fields were grouped in four regions, defined according to similar geological formations, named Seashore, Center, Highland and West. The values of the macronutrients P, K, Ca and Mg and of the micronutrients Zn, Cu, Mn and Fe, determined in the soil samples, were grouping in interpretation classes established by the “Comissão de Química e Fertilidade do Solo do Núcleo Regional Sul da Sociedade Brasileira de Ciência do Solo”. In general, the relative distribution of soil P content is similar among regions, with greater relative amount of the high and very high P ranges in the West and low and very low in the Highland. Medium to very high K content ranges were found in more than 90% of the fi elds, except in the Seashore, where was found near 60% of the fields in these ranges. Similar distribution to the K also was found for exchangeable Ca and Mg content among ranges and regions. For the micronutrients, only Cu shown high relative distribution of the low content ranges, mainly in the Seashore and Center regions, which is probably related to the characteristics of the geological formations.